Cebpb Regulates Skeletal Stem Cell Osteogenic Differentiation and Fracture Healing via the WNT/β-Catenin Pathway - Jiansong Wang; Chensong Yang; Fanyu Kong; Zhi Zhang; Shengchao Ji; Guixin Sun (Stem Cells International)
Fracture is the most common traumatic organ injury, and fracture nonunion is a critical clinical challenge. The research on the mechanisms of skeletal stem cell (SSC) differentiation and fracture healing may help develop new treatment strategies and improve the prognosis of patients at high risk of nonunion. Bioinformatic analysis of scRNA-seq data of mouse SSCs and mouse osteoprogenitors was applied to discover major transcription factors for the regulation of SSC differentiation. FACS was used to isolate SSCs prospectively. The expression of Cebpb, osteogenesis-related genes (Runx2, Sp7, and Bglap2), and markers for Notch, Hedgehog, MAPK, BMP2/SMAD, and WNT/β-catenin signaling pathways (Hes1, Gli1, p-Erk1/2, p-Smad1/5/9, and β-catenin) were detected in SSCs with qPCR or western blot, respectively. Alkaline phosphatase assay and alizarin red S staining were used to illustrate the osteogenic differentiation ability of SSCs in vitro. A WNT inhibitor, IWR-1, was further used to explore the mechanism of WNT signaling in the differentiation of SSCs. Micro-CT, mechanical testing, and immunohistochemistry of osteogenic and chondrogenic proteins (Sp7 and Col2α1) were used to demonstrate the capacity of Cebpb knockdown in promoting fracture healing in a monocortical defect model. We found that Cebpb was the crucial transcription factor regulating SSC differentiation. Inhibiting Cebpb in SSCs enhanced the expression of active β-catenin to promote the expression of WNT target genes, thus facilitating the osteogenic differentiation of SSCs. Bone mass, mechanical properties, and osteogenic protein expression were also increased in the Cebpb inhibition group compared to the group without Cebpb inhibition. Collectively, our results proved that Cebpb knockdown promotes SSC osteogenic differentiation and fracture healing via the WNT/β-catenin signaling pathway.